Evaluasi Implementasi Kurikulum 2013 pada Mata Pelajaran Matematika Di SMP Negeri - Apriyani Lisnawati Mowendu; Slameto Slameto; Yari Dwikurnaningsih (Universitas Kristen Satya Wacana, 2019)
Curriculum 2013 is one of government’s strategic to decrease the quality of education. SMP Negeri 7 Salatiga is one of school that has implemendted the curriculum since 2014. This evaluation research departs from the problem that found on implementation of curriculum 2013 at SMP Negeri 7 Salatiga, especially on math. The purpose of this study is to describes the implementation of curriculum 2013, especially on math subject at SMP Negeri 7 Salatiga. The subjects of this research are the student and math teachers in SMP Negeri 7 Salatiga. Data collection techniques used in this research were interviews, observation, questionnaires and documentation. Data analysis technique used in this research is descriptive qualitative. This study describes how the implementation of curriculum 2013 in schools is based on model of countenance stake evaluation and is guided by the standards that used. The results showed that: 1) at the antecedents stage, 100% meet the standards of the kurikulum 2013 tools and lesson planning; 2) at the transaction stage, 40% have not met the standards for learning implementation and 40% have not met the standards for the authentic assessment; 3) at the outcomes stage of 83.3% not meeting the standards for authentic assessment results.